Forward-looking budget for agrarian sector - Srinivasan, G. (kurukshetra)
The Union budget 2020-21 heralds, a progressive phase for the country's agrarian and revival of the rural economy as they constitute the constitute the vibrant and dynamic segments of the overall economy. The various pro-farmer policies and incentives would indubitably help ignite the growth momentum of the country's farm sector so that it would redound to the building up of the economy in a sturdy way. - Reproduced
Keywords: Budget, Agriculture - India